Gender Bias in SME Lending : Experimental Evidence from Turkey - Alibhai, Salman; Donald, Aletheia; Goldstein, Markus; Oguz, Alper Ahmet; Pankov, Alexander; Strobbe, Francesco (World Bank, Washington, DC, 2020)
Gender disparities in small and medium-size enterprise lending exist around the world and impede the growth of millions of women-led firms. This paper examines a potential driver of these disparities: gender-biased loan officers. Officer bias is measured through a novel loan application experiment conducted with 77 loan officers in Turkish banks. The analysis finds that 35 percent of the loan officers are biased against female applicants, with women receiving loan amounts $14,000 lower on average compared with men. Experience in the banking sector can attenuate this bias, with each year of experience reducing gender biased loan allocations by 6 percent. The results suggest that loan officers may use gender bias as a heuristic device given limited information and risk aversion. Helping newly recruited and lesser experienced loan officers to better discern loan application quality may thus improve financing of business loans to women and reduce gender gaps in entrepreneurship.